1980
DOI: 10.1136/thx.35.10.768
|View full text |Cite
|
Sign up to set email alerts
|

Reversible airway obstruction in cystic fibrosis.

Abstract: Fourteen (29 %) of 48 children with cystic fibrosis had a greater than 15 % improvement in forced expiratory volume in one second, or in forced vital capacity after inhalation of salbutamol. All these children were atopic (one or more positive prick tests) and had a significantly higher mean serum IgE than either non-atopic subjects or those atopic subjects without airways reversibility (p < 0 02). Half of those with airways reversibility had or subsequently developed the clinical picture of allergic bronchopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In vivo measurements of bronchial responsiveness in CF patients demonstrate that smooth muscle shortening occurs, since a large percentage of CF patients show an increased response to bronchodilators [30,31,34,40]. This implies that under baseline conditions the smooth muscle is shortened to some extent.…”
Section: Airway Dimensions Airflow Obstruction and Bronchial Responsmentioning
confidence: 99%
“…In vivo measurements of bronchial responsiveness in CF patients demonstrate that smooth muscle shortening occurs, since a large percentage of CF patients show an increased response to bronchodilators [30,31,34,40]. This implies that under baseline conditions the smooth muscle is shortened to some extent.…”
Section: Airway Dimensions Airflow Obstruction and Bronchial Responsmentioning
confidence: 99%
“…Although this represents a very high prevalence, asthma is much more common in children with CF, where the rate of bronchial hyper-responsiveness approaches 50%, and up to 10-15% may experience a hyper-IgE asthma variant known as allergic bronchopulmonary aspergillosis (ABPA). [29][30][31][32][33][34][35][36][37][38][39][40] ABPA is characterized by a predominantly Th2-mediated immune response to inhaled Aspergillus antigens in the airways, leading to reversible airway obstruction and bronchial hyper-reactivity. This inflammatory response correlates with the local infiltration of effector cells including mast cells, activated neutrophils, eosinophils, basophils and macrophages into the airway mucosa and the airway lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have shown that only a minority of children respond with an improvement in lung function after inhaling a bronchodi lator and in most cases this improvement is small (5,6,(19)(20)(21)(22), There is some evi dence that bronchodilators increase air way instability by increasing the compli ance of the larger airways and this may ex plain differences in response measured by SGaw and tests of forced expiratory flow [7,19,23]. Theophylline has been reported to improve lung function when given in travenously [24] but was associated with deterioration and marked side effects in some patients when given orally on a regu lar basis [5,25].…”
Section: Discussionmentioning
confidence: 99%